Influence of Culture and Organization Commitment to Performance Managgement of The Covid-19 Pandemic in The Bekasi City Manpower Office - Andrie Kurniawan; Kurniawan Prambudi Utomo; Sinta Rukiastiandari (Publisher Cv. Inara, 2021)
This study aims to determine the effect of work culture and organizational commitment on public management performance, using quantitative descriptive analysis method, with 50 respondents from the Department of Manpower's employees to obtain data both primary and secondary then processed with multiple regression and correlation. There is a positive and significant relationship between the independent variables, namely culture and commitment to the dependent variable, namely management performance, but there are still unsatisfactory valuesThe name of this article is:in organizational commitment, this will be a challenge for the Office to continue to make competency-based performance changes and create a healthy and good bureaucracy.